Ferroelectric-coated positive electrode material and application of ferroelectric-coated positive electrode material in high-temperature safe solid-state battery

By covering the positive electrode material of all solid state batteries with ferroelectric-simultaneous phase transition and high-temperature melting behavior, the problem of thermal runaway at high temperatures is solved, and high energy density and cycle at safe temperatures are achieved Stability and effectively block lithium ion transmission at high temperatures improve the high temperature safety of the battery.

CN119419238APending Publication Date: 2025-02-11QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411520324.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

All-solid-state batteries still have the risk of thermal runaway at high temperatures. The existing PTC materials have low conductivity and large leakage current at room temperature, which limits the safety and energy density of the battery.

Method used

The positive electrode material is coated with ferroelectric-simultaneous phase change behavior and high-temperature melting behavior. The ferroelectric is distributed in a discontinuous island form on the surface of the positive electrode material, forming a built-in electric field of ferroelectric to regulate lithium ion transmission, and Transform to block the paraelectric phase or molten state of lithium ions at high temperature.

Benefits of technology

Improve lithium ion transmission at safe temperatures, reduce the interface reaction between the positive electrode and the electrolyte, improve the energy density and cycle stability of all solid-state batteries, and effectively block lithium ion transmission at high temperatures, reduce heat accumulation, and improve the high temperature of the battery Security.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419238A_ABST
    Figure CN119419238A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrode materials, in particular to a ferroelectric-coated positive electrode material with a ferroelectric-paraelectric phase change behavior and a high-temperature melting behavior and application of the ferroelectric-coated positive electrode material in a high-temperature safe solid-state battery. Ferroelectric bodies with a temperature-triggered phase change behavior and an ultrahigh-temperature melting behavior are distributed and wrapped on the surfaces of the positive electrode material particles in a discontinuous island form; wherein the mass ratio of the ferroelectric to the positive electrode material particles is (0.01: 1)-(0.15: 1). According to the method, the phase change behavior and the melting behavior of the ferroelectric material are utilized, the capacity of the solid-state battery is improved at the safe temperature, the capacity of the solid-state battery is inhibited at the high dangerous temperature, and the capacity of the solid-state battery is further inhibited at the thermal runaway temperature, so that the safety design of the solid-state battery is realized, and the method has good research value and application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to a ferroelectric-coated positive electrode material having ferroelectric-paraelectric phase transition behavior and high-temperature melting behavior, and application thereof in high-temperature safe solid-state batteries. Background Art

[0002] Because the electrolyte has high fluidity and flammability, traditional liquid batteries are prone to combustion or even explosion when colliding and squeezing. The exothermic reaction at the interface between the positive electrode and the electrolyte is considered to be one of the main factors causing the battery temperature to rise. Therefore, directly responding to the temperature change at the interface between the positive electrode and the electrolyte can more quickly curb the process of battery thermal runaway. In recent years, all-solid-state batteries have been considered to be the most promising next-generation energy storage technology because of their high safety and high energy density. This is because the solid electrolyte used is more stable and non-flammable than traditional organic electrolytes. However, with the deepening of research, people have found that all-solid-state batteries are not as safe as expected, and there is still a risk of thermal runaway at high temperatures. Document 1 (Electrochimica Acta 2015, 186, 404-412) shows that lithium-ion batteries release heat during both charging and discharging. The increase in temperature will trigger a series of side reactions, which is one of the causes of battery thermal runaway. Therefore, blocking the transmission of lithium ions at high temperatures is the most effective strategy to avoid thermal runaway. The most widely used method is to use a positive temperature coefficient (PTC) material as a modified layer of the current collector. The resistance of this type of material increases with increasing temperature, and electron transmission can be cut off at high temperatures. For example, in Patent Document 2 (Publication No.: CN107644972-A), a solid-state battery is disclosed, in which a layer of PTC material containing an inorganic insulator is laid between the current collector layer and the electrode active material layer, and the electronic conductivity of the battery is significantly improved when the temperature rises. However, the PTC layer usually has poor conductivity and large leakage current at room temperature, which greatly reduces the capacity of the battery at a safe temperature, thereby limiting its application. In addition, coating materials that do not have ion / electron transmission capabilities are often coated on the surface of the positive electrode in a discontinuous form, thereby reserving certain ion / electron transmission channels for the battery to operate at normal temperatures. However, this non-fully coated functional layer means that there are still reaction sites between the positive electrode and the electrolyte at high temperatures, because the risk of thermal runaway of the battery cannot be completely eliminated. Summary of the invention

[0003] To solve the above problems, the present invention provides a ferroelectric-coated positive electrode material having ferroelectric-paraelectric phase transition behavior and high-temperature melting behavior, and its application in high-temperature safe solid-state batteries.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] A ferroelectric-coated positive electrode material, wherein the surface of the positive electrode material particles is covered with a ferroelectric having temperature-triggered phase change behavior and ultra-high temperature melting behavior in a discontinuous island form; wherein the mass ratio of the ferroelectric to the positive electrode material particles is between 0.01:1 and 0.15:1.

[0006] The ferroelectric with temperature-triggered phase transition behavior and ultra-high temperature melting behavior is a ferroelectric with a ferroelectric-paraelectric phase transition temperature of 70-150° C. and a melting point of more than 150° C.

[0007] The size of the discontinuous island-shaped ferroelectric on the surface of the positive electrode material particles is between 1 and 500 nm, and the distance between two adjacent particles is greater than 1 nm.

[0008] The ferroelectric material is (C6H 14 N)2PbBr4, (NH2CH2COOH)3H2SO4, [C(NH2)3]4Cl2SO4, (C8H 20 N)ClO4、(C6H 12 N2)ClO4, (C3H4N2)IO4, (C3H4N2)ClO4 or more thereof.

[0009] The ferroelectric material should absorb heat when undergoing ferroelectric-paraelectric phase transition and melting.

[0010] According to the above-mentioned ferroelectric materials, (C3H4N2)ClO4 (abbreviated as ImClO4) is preferred.

[0011] The ferroelectric-paraelectric phase transition temperature of the ferroelectric material is 105°C and the melting point is 220°C.

[0012] The positive electrode material is at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium cobalt manganese oxide, lithium iron phosphate, lithium-rich manganese-based material, and nickel manganese spinel.

[0013] The ferroelectric with ferroelectric-paraelectric phase transition behavior and high-temperature melting behavior is located at the interface between the positive electrode and the electrolyte, wrapping the positive electrode material particles to construct a ferroelectric built-in electric field, promoting lithium ion transmission between the positive electrode and the electrolyte, and the exothermic reaction between the two can be accurately responded to in the first time.

[0014] The particle size or thickness of the ferroelectric coating layer should be smaller than the particle size or thickness of the positive electrode particles.

[0015] A method for preparing the ferroelectric coated positive electrode material comprises dissolving the ferroelectric in a solution, adding the positive electrode active material under continuous stirring and mixing, and then completely evaporating the solvent to obtain the ferroelectric coated positive electrode material between the positive electrode and the electrolyte.

[0016] The solution is a polar solvent such as water, ethanol, acetone, acetonitrile, etc.

[0017] The ferroelectric-coated positive electrode material can be prepared by a variety of techniques, including but not limited to solvent evaporation, spin coating, sol-gel method, hydrothermal method, solvothermal method, chemical solution deposition method, magnetron sputtering, pulsed laser deposition method, molecular beam epitaxy, vapor deposition method, transfer technology, etc.

[0018] An application of the ferroelectric-coated positive electrode material, and an application of the ferroelectric-coated positive electrode material in a solid-state battery.

[0019] The ferroelectric-paraelectric phase transition and melting process of the ferroelectric in the ferroelectric-coated positive electrode material absorb heat, and the application in achieving the safety of solid-state batteries.

[0020] A solid-state battery consists of a positive electrode, a negative electrode and a solid electrolyte, wherein the positive electrode comprises a positive electrode material coated with a ferroelectric.

[0021] The solid electrolyte used should be a solid electrolyte in the battery field, preferably a sulfide electrolyte.

[0022] Excellent effects of the present invention

[0023] Ferroelectrics are combined with positive electrode material particles through electrostatic effects, hydrogen bonds or chemical bonds, forming a discontinuous island distribution on the surface of the positive electrode material. The ferroelectric layer maintains a stable ferroelectric phase at a safe temperature, has spontaneous ferroelectric polarization, forms a ferroelectric built-in electric field, improves lithium ion transmission at a safe temperature, and has a positive effect on reducing the interface reaction between the positive electrode and the electrolyte and improving the energy density and cycle stability of all-solid-state batteries. When the internal temperature of the battery rises above the ferroelectric-paraelectric phase transition temperature of the ferroelectric, the ferroelectric coating layer is transformed into a non-polar dielectric coating layer, and the ferroelectric built-in electric field disappears, hindering the transmission of lithium ions, thereby achieving the purpose of reducing the heat generation reaction during the charging and discharging process, reducing the internal heat accumulation of the solid-state battery, and improving the high-temperature safety of the battery. When the temperature inside the battery continues to rise above the melting temperature of the ferroelectric, the ferroelectric material coated on the surface of the positive electrode will change from an island particle structure to a molten state with fluidity. At this time, the material will fully coat the surface of the positive electrode particles, thereby completely cutting off the transmission of lithium ions, causing the battery to stop working and the exothermic reaction to terminate. Compared with materials such as paraffin that have high-temperature melting properties but lack low-temperature ferroelectricity, ferroelectric coating materials can ensure the normal performance of batteries at safe temperatures. Compared with the preparation of an electrolyte layer with temperature-responsive characteristics, this high-temperature safety design based on the positive electrode ferroelectric coating layer reacts more quickly and can ensure the safety of the battery to a greater extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1Schematic diagram of the working principle of the ferroelectric coating at room temperature, high temperature and ultra-high temperature, wherein Figure a is a schematic diagram of the ferroelectric coating enhancing ion transport at room temperature, Figure b is a schematic diagram of the ferroelectric coating transforming into a paraelectric phase at high temperature to hinder ion transport, and Figure c is a schematic diagram of the ferroelectric coating transforming into a molten state at ultra-high temperature to completely block lithium ion transport.

[0025] Figure 2 Scanning images of the wrapped positive electrode material and the bare positive electrode material provided in the embodiments of the present invention, wherein a is the SEM image of the bare LiCoO2 particles provided in the comparative example 1 of the present invention; b is the SEM image of the 2wt% ImClO4 coated LiCoO2 particles provided in the embodiment 1 of the present invention; c is the EDS element distribution spectrum of Co in the 2wt% ImClO4 coated LiCoO2 particles provided in the embodiment 1 of the present invention; d is the EDS element distribution spectrum of Cl in the 2wt% ImClO4 coated LiCoO2 particles provided in the embodiment 1 of the present invention.

[0026] Figure 3 ARC test results of the 10wt% ImClO4-coated LiCoO2 composite positive electrode provided in Example 3 of the present invention and the bare LiCoO2 solid-state lithium battery of Comparative Example 1.

[0027] Figure 4 The DSC test results of different ferroelectric materials are shown in Figure a. The optimized ferroelectric material is ImClO4, the ferroelectric material is TEAClO4, and the ferroelectric material is GClO4. DETAILED DESCRIPTION

[0028] In order to more clearly illustrate the technical features and performance improvement effects of the present invention, the present invention will be further described in detail below with reference to specific embodiments and drawings.

[0029] The ferroelectric-coated positive electrode material and the solid-state battery assembled therefrom of the present invention utilize the ferroelectric-paraelectric phase transition behavior and high-temperature melting behavior of the ferroelectric to intelligently and stage-by-stage control the lithium ion transmission behavior of the solid-state battery at different temperatures.

[0030] The present invention is compared and studied in detail using organic-inorganic hybrid ferroelectric ImClO4 as the ferroelectric coating layer. ImClO4 is a hydrogen-bonded organic-inorganic ferroelectric with a reported ferroelectric-paraelectric phase transition temperature of 105°C and a melting point of 340°C.

[0031] Example 1: 2wt% ImClO4 coated LiCoO2 cathode particles (2Im@LCO)

[0032] Weigh 0.039 g of commercially available ferroelectric ImClO4 powder and dissolve it in ethanol. Continue heating and stirring at 50°C until the powder is dissolved.

[0033] Weigh 1.957g of commercially available positive electrode powder (LiCoO2) and immerse it in the above solution, continue to heat and stir at 50℃ until the solvent evaporates completely. Transfer the obtained sample to an oven, first dry it at 60℃ for 1h to remove the residual solvent, then anneal it at 80℃ for 5h, and cool it to room temperature with the furnace. Finally, the ferroelectric ImClO4-coated LiCoO2 positive electrode material is obtained, and the mass ratio of ImClO4 to LiCoO2 is about 0.02:1 (0.039g:1.957g).

[0034] Example 2: 6wt% ImClO4 coated LiCoO2 cathode particles (6Im@LCO)

[0035] Weigh 0.117 g of commercially available ferroelectric ImClO4 powder and dissolve it in ethanol. Continue heating and stirring at 50°C until the powder is dissolved.

[0036] Weigh 1.957g of commercially available positive electrode powder (LiCoO2) and immerse it in the above solution, continue heating and stirring at 50℃ until the solvent evaporates completely. Transfer the obtained sample to an oven, first dry it at 60℃ for 1h to remove the residual solvent, then anneal it at 80℃ for 5h, and cool it to room temperature with the furnace. Finally, the ferroelectric ImClO4-coated LiCoO2 positive electrode material is obtained, and the mass ratio of ImClO4 to LiCoO2 is about 0.06:1 (0.117g:1.957g).

[0037] Example 3: 10wt% ImClO4 coated LiCoO2 cathode particles (10Im@LCO)

[0038] Weigh 0.195 g of commercially available ferroelectric ImClO4 powder and dissolve it in ethanol. Continue heating and stirring at 50°C until the powder is dissolved.

[0039] Weigh 1.957g of commercially available positive electrode powder (LiCoO2) and immerse it in the above solution, continue to heat and stir at 50℃ until the solvent evaporates completely. Transfer the obtained sample to an oven, first dry it at 60℃ for 1h to remove the residual solvent, then anneal it at 80℃ for 5h, and cool it to room temperature with the furnace. Finally, the ferroelectric ImClO4-coated LiCoO2 positive electrode material is obtained, and the mass ratio of ImClO4 to LiCoO2 is about 0.1:1 (0.195g:1.957g).

[0040] Example 4: 15wt% ImClO4 coated LiCoO2 cathode particles (15Im@LCO)

[0041] Weigh 0.2925 g of commercially available ferroelectric ImClO4 powder and dissolve it in ethanol. Continue heating and stirring at 50°C until the powder is dissolved.

[0042] Weigh 1.957g of commercially available positive electrode powder (LiCoO2) and immerse it in the above solution, continue to heat and stir at 50℃ until the solvent evaporates completely. Transfer the obtained sample to an oven, first dry it at 60℃ for 1h to remove the residual solvent, then anneal it at 80℃ for 5h, and cool it to room temperature with the furnace. Finally, the ferroelectric ImClO4-coated LiCoO2 positive electrode material is obtained, and the mass ratio of ImClO4 to LiCoO2 is about 0.15:1 (0.2925g:1.957g).

[0043] Example 5: 10wt% ImClO4 coated LiNi 0.8 Co 0.1 Mn 0.1 O2 cathode particles (10Im@NCM)

[0044] Weigh 0.195 g of commercially available ferroelectric ImClO4 powder and dissolve it in ethanol. Continue heating and stirring at 50°C until the powder is dissolved.

[0045] Weigh the commercially available positive electrode powder (LiNi 0.8 Co 0.1 Mn 0.1 O2) 1.957g was immersed in the above solution, and continued to heat and stir at 50℃ until the solvent evaporated completely. The obtained sample was transferred to an oven, first dried at 60℃ for 1h to remove the residual solvent, then annealed at 80℃ for 5h, and cooled to room temperature in the furnace. Finally, the ferroelectric ImClO4-coated LiNi 0.8 Co 0.1 Mn 0.1 O2 cathode materials, ImClO4 and LiNi 0.8 Co 0.1 Mn 0.1 The mass ratio of O2 is approximately 0.1:1 (0.195g:1.957g).

[0046] Example 6: 10wt% ImClO4 coated LiFePO4 positive electrode particles (10Im@LFP)

[0047] Weigh 0.195 g of commercially available ferroelectric ImClO4 powder and dissolve it in ethanol. Continue heating and stirring at 50°C until the powder is dissolved.

[0048] Weigh 1.957g of commercially available positive electrode powder (LiFePO4) and immerse it in the above solution, continue heating and stirring at 50℃ until the solvent evaporates completely. Transfer the obtained sample to an oven, first dry it at 60℃ for 1h to remove the residual solvent, then anneal it at 80℃ for 5h, and cool it to room temperature with the furnace. Finally, the ferroelectric ImClO4-coated LiFePO4 positive electrode material is obtained, and the mass ratio of ImClO4 to LiFePO4 is about 0.1:1 (0.195g:1.957g).

[0049] Comparative Example 1: Bare LiCoO2 cathode particles (Bare LCO)

[0050] Weigh 1.957 g of commercially available positive electrode powder (LiCoO2) and immerse it in an ethanol solution. Continue heating and stirring at 50°C until the solvent evaporates completely. Transfer the obtained sample to an oven, first dry it at 60°C for 1 hour to remove the residual solvent, then anneal it at 80°C for 5 hours, and cool it to room temperature in the oven. Collect the powder.

[0051] Comparative Example 2: Bare LiNi 0.8 Co 0.1 Mn 0.1 O2 cathode particles (Bare NCM)

[0052] Weigh the commercially available positive electrode powder (LiNi 0.8 Co 0.1 Mn 0.1 O2) 1.957g was immersed in an ethanol solution and heated and stirred at 50°C until the solvent evaporated completely. The obtained sample was transferred to an oven and dried at 60°C for 1h to remove the residual solvent, then annealed at 80°C for 5h and cooled to room temperature in the oven. The powder was collected.

[0053] Comparative Example 3: Bare LiFePO4 cathode particles (Bare LFP)

[0054] Weigh 1.957 g of commercially available positive electrode powder (LiFePO4) and immerse it in an ethanol solution. Continue heating and stirring at 50°C until the solvent evaporates completely. Transfer the obtained sample to an oven, first dry it at 60°C for 1 hour to remove the residual solvent, then anneal it at 80°C for 5 hours, and cool it to room temperature in the oven. Collect the powder.

[0055] Comparative Example 4: 10wt% TEAClO4 coated LiCoO2 positive electrode particles (10TEA@LCO)

[0056] Weigh 0.195 g of commercially available ferroelectric TEAClO4 powder and dissolve it in ethanol. Continue heating and stirring at 50°C until the powder is dissolved.

[0057] Weigh 1.957g of commercially available positive electrode powder (LiCoO2) and immerse it in the above solution, continue heating and stirring at 50℃ until the solvent evaporates completely. Transfer the obtained sample to an oven, first dry it at 60℃ for 1h to remove the residual solvent, then anneal it at 80℃ for 5h, and cool it to room temperature with the furnace. Finally, the ferroelectric TEAClO4-coated LiCoO2 positive electrode material is obtained, and the mass ratio of TEAClO4 to LiCoO2 is about 0.1:1 (0.195g:1.957g).

[0058] Comparative Example 5: 10wt% GClO4 coated LiCoO2 cathode particles (10G@LCO)

[0059] Weigh 0.195 g of commercially available ferroelectric GClO4 powder and dissolve it in ethanol. Continue heating and stirring at 50°C until the powder is dissolved.

[0060] Weigh 1.957g of commercially available positive electrode powder (LiCoO2) and immerse it in the above solution, continue heating and stirring at 50℃ until the solvent evaporates completely. Transfer the obtained sample to an oven, first dry it at 60℃ for 1h to remove the residual solvent, then anneal it at 80℃ for 5h, and cool it to room temperature with the furnace. Finally, the ferroelectric GClO4-coated LiCoO2 positive electrode material is obtained, and the mass ratio of GClO4 to LiCoO2 is about 0.1:1 (0.195g:1.957g).

[0061] Application example: Using the positive electrode powder synthesized in the above embodiment and comparative example as the positive electrode, Li6PS5Cl as the solid electrolyte, and lithium boron indium alloy as the negative electrode, a solid-state battery is assembled and the battery performance is tested. The application effect of the present invention is described in detail in conjunction with the accompanying drawings.

[0062] Preparation of composite positive electrode: The positive electrode material obtained in the above examples or comparative examples, Li6PS5Cl powder and conductive agent (VGCF) were uniformly mixed in agate mortar for 30 minutes in a certain ratio to prepare composite positive electrode. Among them, the ratio of LiCoO2-based composite positive electrode is 7:3:0, LiNi 0.8 Co 0.1 Mn 0.1 The ratio of O2 and LiFePO4 based composite positive electrode is 7:3:0.3.

[0063] Assembly of solid-state battery: First, 80 mg of sulfide solid electrolyte Li6PS5Cl powder was added to the battery mold and uniaxially pressed at 150 MPa for 2 min. 10 mg of the above mixed powder was evenly spread on one side of the above-mentioned Li6PS5Cl electrolyte sheet, and then uniaxially pressed at 370 MPa for 2 min. After the second pressing step, a thin indium foil (0.1 mm) with a diameter of 9 mm and a thin lithium boron sheet (0.25 mm) with a diameter of 3 mm were added to the other side of the Li6PS5Cl electrolyte sheet in turn and pressed at 150 MPa for 2 min. After that, a stainless steel frame was used to fix the battery and a constant pressure was applied by tightening the nut, which remained unchanged during the electrochemical test.

[0064] Testing of solid-state batteries: The above-mentioned assembled batteries were all tested for performance using the Land battery testing system. The battery test rate was 0.2C and the voltage range was 2.0-3.7V. The test results of solid-state batteries at different temperatures are summarized in Tables 1 and 2. Considering that the phase transition temperature of the ferroelectric ImClO4 is 105°C, the battery tests were set at 30°C and 115°C, respectively. Considering that the melting point of the ferroelectric ImClO4 is 187°C, it is far beyond the conventional battery test temperature range. In order to investigate the inhibitory effect of the ImClO4 coating on battery thermal runaway at ultra-high temperatures, the batteries before and after modification were experimentally subjected to accelerated calorimetry (ARC) tests to observe the changes in the thermal runaway temperature of the battery under external heating conditions.

[0065] Table 1. Comparison of the capacity of the batteries of Example 1 and Comparative Example 1 at different cycle numbers at room temperature

[0066] Number of laps <![CDATA[Example 1 (mAh g -1 )]]> <![CDATA[Comparative Example 1 Battery (mAh g -1 )]]> 1 115.9 112.3 10 113.6 108.2 50 112.4 96.5 100 111.8 92.8 200 110.3 88.3

[0067] Table 2. Comparison of capacity changes of all-solid-state batteries when charged at room temperature 30°C and discharged at high temperature 115°C (discharge rate is 0.2C)

[0068]

[0069]

[0070] like Figure 1 As shown in a, the ferroelectric coating layer is distributed in the form of islands on the surface of the positive electrode material particles. Affected by factors such as the unit cell parameters between the ferroelectric and the positive electrode material particles, the ferroelectric dipoles of the ferroelectric will be arranged at a certain angle on the surface of the positive electrode particles, thereby forming a ferroelectric built-in electric field to regulate lithium ion transmission. When the temperature rises, the material transforms into a paraelectric phase ( Figure 1 b), the ferroelectric coating will become a paraelectric dielectric layer, hindering the transmission of lithium ions and improving the high-temperature stability of the battery. If the battery temperature rises further and there is a trend of thermal runaway, the paraelectric coating will turn into a molten state, the coating will flow and connect together, forming a continuous package on the positive electrode surface. At this time, the contact between the positive electrode and the electrolyte is completely blocked, the battery stops working, and thermal runaway is quickly suppressed.

[0071] Figure 2 a SEM image of the bare LiCoO2 particles used. It can be seen from the figure that the bare LiCoO2 particles are irregular polyhedral particles with a relatively smooth surface and a particle size of about 6μm. Figure 2 After being coated with 2wt% ImClO4 in b, the LiCoO2 particles have obvious island-like particle distribution, proving that the ferroelectric material has been discontinuously coated on its surface. Figure 2c and 2d respectively characterize the distribution of Co and Cl elements in the 2wt% ImClO4-coated LiCoO2 particles of Example 1, proving that ImClO4 is dispersed more evenly on the LiCoO2 surface.

[0072] The ferroelectric coated positive electrode material obtained in Example 1 and the comparative example bare LiCoO2 positive electrode battery were subjected to charge and discharge tests at a voltage range of 2-3.7V and a rate of 0.2C. First, the regulating effect of the ferroelectric coating on the interface between the positive electrode and the electrolyte was verified. As shown in Table 1, although the discharge capacity of the bare LiCoO2 positive electrode in the first cycle is 112.3 mAh g -1 However, as the number of cycles increases, the interface side reactions between the positive electrode and the electrolyte intensify and high-resistance byproducts continue to accumulate, resulting in a continuous decline in battery capacity. After 200 cycles, the capacity of the bare LiCoO2 positive electrode battery has dropped to 88.3 mAh g -1 , the capacity retention rate is only 78%. Under the same conditions, the stability of the battery in Example 1 is relatively strong, and after 200 cycles, the capacity retention rate of the battery is as high as 95%.

[0073] The performance of each battery at different temperatures is shown in Table 2. At room temperature, all all-solid-state batteries coated with ferroelectric materials have improved capacity. For example, the discharge capacity of the 6Im@LCO all-solid-state battery in Example 2 is 128.9 mAh g -1 , which is significantly higher than the capacity of bare LiCoO2 cathode battery under the same conditions (112.3 mAh g -1 . When the temperature rises to a dangerous temperature (115°C), ImClO4 transforms from a ferroelectric phase to a paraelectric phase, hindering the transmission of lithium ions. The results show that the discharge specific capacities of Examples 1-4 are significantly reduced. In comparison, Example 3 has higher performance at room temperature and obvious blocking effect at high temperature. Ferroelectric materials have obvious high-temperature protection for different types of positive electrode materials. In order to further compare the improvement effect of coated ferroelectric materials on the high-temperature thermal runaway performance of the battery, ARC tests were performed on Example 3 and Comparative Example 1 ( Figure 3 ). The test results show that the T1 and T2 temperatures of the modified battery are more delayed, and the time difference between T1 and T2 is larger, indicating that thermal runaway is suppressed.

[0074] In addition, there are certain differences in the thermodynamic behavior of different organic-inorganic hybrid ferroelectric materials, which makes them perform differently in regulating the high-temperature safety of solid-state lithium batteries. Two ferroelectric materials in Comparative Examples 4 and 5 coated the LCO positive electrode and tested the temperature performance of the battery under the same conditions. The ferroelectric material used in Comparative Example 4 is TEAClO4, which has a phase transition temperature of 107°C and thus also has a significant blocking effect. However, this material will release a large amount of heat when it melts (290°C), which will undoubtedly accelerate the high-temperature thermal runaway of the battery ( Figure 4 ). The material used in Comparative Example 5 is GClO4, which undergoes a ferroelectric-paraelectric phase transition and absorbs heat at 180°C. However, this phase transition temperature is too late for the first high-temperature blocking step of the battery. In contrast, the ferroelectric-paraelectric phase transition temperature of the ferroelectric material ImClO4 used in the embodiment is 105°C, which corresponds well to the starting temperature of high-temperature thermal runaway of solid-state lithium batteries. And ImClO4 undergoes obvious heat absorption during the ferroelectric-paraelectric phase transition and melting process, which is beneficial for suppressing high-temperature thermal runaway of solid-state lithium batteries.

[0075] The specific embodiments and drawings of the present invention disclosed above are intended to help understand the content of the present invention and implement it accordingly. Those skilled in the art can make various substitutions, changes and modifications within the scope of the present invention without departing from the spirit and scope of the present invention. The present invention should not be limited to the contents disclosed in the embodiments and drawings of this specification, and the scope of protection of the present invention shall be subject to the scope defined in the claims.

Claims

1. A ferroelectric-coated positive electrode material, characterized in that: The surface of the positive electrode material particles is distributed and wrapped with a ferroelectric having temperature-triggered phase change behavior and ultra-high temperature melting behavior in a discontinuous island form; wherein the mass ratio of the ferroelectric to the positive electrode material particles is between 0.01:1 and 0.15:

1.

2. The ferroelectric-coated positive electrode material according to claim 1, characterized in that: The ferroelectric with temperature-triggered phase transition behavior and ultra-high temperature melting behavior is a ferroelectric with a ferroelectric-paraelectric phase transition temperature of 70-150° C. and a melting point of more than 150° C.

3. The ferroelectric-coated positive electrode material according to claim 1, characterized in that: The size of the discontinuous island-shaped ferroelectric on the surface of the positive electrode material particles is between 1 and 500 nm, and the distance between two adjacent particles is greater than 1 nm.

4. The ferroelectric-coated positive electrode material according to any one of claims 1 to 4, characterized in that: The ferroelectric material is (C6H 14 N)2PbBr4, (NH2CH2COOH)3H2SO4, [C(NH2)3]4Cl2SO4, (C8H 20 N)ClO4、(C6H 12 N2)ClO4, (C3H4N2)IO4, (C3H4N2)ClO4 or more thereof.

5. The ferroelectric-coated positive electrode material according to claim 3, characterized in that: The preferred ferroelectric material is (C3H4N2)ClO4.

6. The ferroelectric-coated positive electrode material according to claim 1, characterized in that: The positive electrode material is at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium cobalt manganese oxide, lithium iron phosphate, lithium-rich manganese-based material, and nickel manganese spinel.

7. A method for preparing the ferroelectric-coated positive electrode material according to claim 1, characterized in that: The ferroelectric is dissolved in the solution, and the positive electrode active material is added and mixed under continuous stirring, and then the solvent is completely evaporated to obtain the positive electrode material coated with the ferroelectric.

8. An application of the ferroelectric-coated positive electrode material according to claim 1, characterized in that: Application of the ferroelectric-coated positive electrode material described in claim 1 in solid-state batteries.

9. The use of the ferroelectric-coated positive electrode material according to claim 8, characterized in that: The ferroelectric-paraelectric phase transition and melting process of the ferroelectric in the ferroelectric-coated positive electrode material absorb heat, and the application in achieving the safety of solid-state batteries.

10. A solid-state battery, which is composed of a positive electrode, a negative electrode and a solid electrolyte, characterized in that: The positive electrode comprises the positive electrode material coated with the ferroelectric according to claim 1.

Citation Information

Patent Citations

  • All solid state battery

    CN107644972A